Mannan oligosaccharide (MOS) on growth performance, immunity, inflammatory and antioxidant responses of the common carp (Cyprinus carpio) under ammonia stress - Xue, Shuqun; Xia, Banghua; Zhang, Bitao; Li, Linyuan; Zou, Yuning; Shen, Zhentao; Xiang, Yifang; Han, Ying; Chen, Weixing (Frontiers in Marine Science, 2022)
This study evaluated the potential effects of mannan oligosaccharide (MOS) on the health status of common carp under ammonia stress. The experimental fish were equally divided into four groups. The control group was fed with a basal diet. The ammonia stress group (Am group) was fed with a basal diet and set in the culture environment with 0.15 mg/L NH3. The MOS group was fed 0.2% MOS with a basal diet. The treatment group (MOS/Am group) was fed 0.2% MOS feed under ammonia exposure (NH3, 0.15 mg/L). These groups were fed for 30 d. The results showed that under ammonia stress, the growth performance decreased significantly, and the activities of non-specific immune factors, intestinal digestive enzymes, and antioxidant enzymes decreased significantly. Dietary supplementation of MOS, the growth performance, the activities of non-specific immune factors, intestinal digestive enzymes, and antioxidant enzymes increased. Histopathological studies showed that adding MOS reduced liver, gill, and intestine tissue damage under ammonia exposure. Our study suggests that adding MOS to the diet can improve growth performance, immunity, antioxidant capacity, and intestinal health of the common carp. MOS can effectively alleviate the oxidative damage and inflammatory response caused by ammonia poisoning to common carp.